Gli2 is required for the induction and migration of Xenopus laevis neural crest - Cerrizuela, Santiago (2018)
The neural crest (NC) is a multipotent migratory embryonic population that is formed during late gastrulation and gives rise to a wide array of derivatives, including cells from the peripheral nervous system (PNS), the craniofacial bones and cartilages, peripheral glial cells, and melanocyte cells, among others. In this work we analyzed the role of the Hedgehog signaling pathway effector gli2 in Xenopus NC. We provide evidence that the gli2 gene is expressed in the prospective, premigratory and migratory NC. The use of a specific morpholino against gli2 and the pharmacological specific inhibitor GANT61 in different experimental approaches allowed us to determine that gli2 is required for the induction and specification of NC cells as a transcriptional activator. Moreover, gli2 also acts by reducing apoptosis in the NC without affecting its cell proliferation status. We also demonstrated that gli2 is required cell-autonomously for NC migration, and for the formation of NC derivatives such as the craniofacial cartilages, melanocytes and the cranial ganglia. Altogether, our results showed that gli2 is a key transcriptional activator to accomplish the proper specification and development of Xenopus NC cells.